(untitled) (INNOVATIVE ECONOMY, 2020)
Pereverzieva A.V. METHODICAL APPROACH TO DETERMINING THE VALUE FOR CREATION OF WORKPLACES IN UNITED TERRITORIAL COMMUNITIES Purpose. The aim of the article is to develop a methodological approach to determining the value of job creation in the united territorial communities and their impact on the level of self-sufficiency. Methodology of research. The use of analytical tools allowed to calculate the cost of creating new workplaces in the united territorial communities on the basis of taking into account certain norms and the level of inflation, as well as the existing employment structure by taking into account. Findings. The structure of employment of communities, which shows that the largest share of labor resources is concentrated in agriculture, in the second place – the trade and service sphere, and in the third – the social sphere, is analyzed. The necessity of creating new workplaces for the purpose of reducing the unemployment rate in the community and achieving the balance between demand and supply of labor is substantiated. The cost of creating new workplaces in the united territorial communities is determined, taking into account the level of inflation. Based on the use of the analytical apparatus, the amount of own income of the community, which is created as a result of the creation of new workplaces, is determined. The result is a reduction in the budget deficit and self-sufficiency. Originality. A methodical approach to calculating the cost of creating new workplaces in the united territorial communities, which allows achieving a balanced budget, and, accordingly, positively affects self-sufficiency, is proposed in the course of the study. Practical value. The method of balancing labor demand and its offer by creating new jobs and quantifying the material costs of implementing this measure, which allows to really evaluate the opportunities of communities and results, is proposed. Key words: cost; personal income; employment; new workplace; united territorial communities; self-sufficiency.